Cognitive Implications of White Matter Alterations in Overweight Chinese Individuals: An NODDI and DTI Study - Shaofan Jiang; Yingzhe Cheng; Rifeng Jiang; Peilin Huang; Jiejun Zhang; Xiaodong Pan; Yunjing Xue (Brain and Behavior)
ABSTRACT Objective: Scarce studies have elucidated the relationship between the microstructure changes of white matter (WM) and cognitive domains in overweight (OW). This study aimed to evaluate the WM microstructure changes and the relationship with the cognitive domains and cognition‐related plasma biomarkers. Methods: This study recruited 77 standard weight (SW) and 42 OW participants. The WM integrity was analyzed using neurite orientation dispersion and density imaging (NODDI) and diffusion tensor imaging (DTI). The region of interest (ROI) values of NODDI and DTI were calculated and compared between groups. The correlations between WM microstructure and cognitive domains and cognition‐related plasma biomarkers were also recorded. Results: The ROI analysis revealed significant differences in fractional anisotropy (FA) and orientation dispersion index (ODI) in extensive WM regions (p < 0.05). Further analysis showed that NODDI parameter values of the uncinate fasciculus (UF) showed significant correlations with the cognitive domain. Additionally, other abnormal WM microstructures of OW were associated with cognitive domains and cognition‐related plasma biomarkers to varying degrees. Conclusion: The findings evidence that abnormalities of the WM microstructure may indicate typical changes of OW, and these microstructure abnormalities are associated with cognitive functions and cognition‐related plasma biomarkers.